2015
DOI: 10.14260/jemds/2015/2453
|View full text |Cite
|
Sign up to set email alerts
|

Study of Diagnostic Tests for Helico B Acter Pylori Infection

Abstract: Helicobacter pylori is the causative agent of most cases of gastritis and peptic ulcer. The diagnosis of H. pylori is an essential element in the management of many common gastrointestinal pathologies. AIMS1. Comparison of invasive and non-invasive tests to choose the appropriate test for the diagnosis of H. pylori infection. 2. Validation of the comparison of the different diagnostic tests. METHODBlood and antral biopsy specimens from 100 acid peptic disease patients and blood samples from 10 control subjects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 5 publications
2
3
0
Order By: Relevance
“…In the current investigation, 18 samples showed positive results for H. pylori culture. The ndings were close to Pilli and Kirani (2015) who showed a 14% positive culture. The antibiotic susceptibility testing is not normally done for initial disease diagnosis, however, it is recommended after the failure of second-line therapy (Thung et al, 2016).…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations
“…In the current investigation, 18 samples showed positive results for H. pylori culture. The ndings were close to Pilli and Kirani (2015) who showed a 14% positive culture. The antibiotic susceptibility testing is not normally done for initial disease diagnosis, however, it is recommended after the failure of second-line therapy (Thung et al, 2016).…”
Section: Discussionsupporting
confidence: 61%
“…The result indicated that urease test showed 44.79% positivity as compared to others which are due to recent or active bleeding and subjects taking drugs (antibiotics or antisecretory compounds) (Suerbaum and Michetti, 2002). This study also correlates with Pilli and Kirani (2015) and Mohsun et al (2011) who reported 36 and 35.6% positivity for the urease test. Gram staining is another rapid screening technique for the judgment of causative agents.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…The prevalence of H. pylori infection as 16% was reported by Ansari et al by stool antigen test [ 16 ]. Another report by Pilli and Kirani showed that 14% of patients were culture positive, 18% were Gram stain positive, 36% were rapid urease test positive, and 42% were serology IgG antibody positive for H. pylori [ 17 ]. The direct Gram-stained smear is an invasive, highly specific, rapid screening test, and in a resource-limited laboratory, a need for additional testing of positive specimens may be avoided.…”
Section: Discussionmentioning
confidence: 99%